Positive Correlation between Very Small Embryonic Stem Cell, Hematopoietic Stem Cell, and Endothelial Progenitor Cell in Umbilical Cord Blood Unit - Angliana Chouw; Bayu Winata Putera; Cynthia Retna Sartika; Ajeng Diantini (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Umbilical Cord Blood (UCB) has been widely use as regenerative medicine due to the content of undifferentiated cell which have capability to do self-renewal and differentiation into various type of cell called stem cells. Recent studies show that UCB contains not only hematopoietic stem cell (HSC) but also others stem cell and progenitor cell such as endothelial progenitor cell (EPC) and very small embryonic-like stem cell (VSEL). It is beliefs that HSC and EPC shared the same progenitor. In this study, correlation between the cell number of HSC, EPC and VSEL is analyzed in umbilical cord blood as the source of stem cell for clinical application.METHODS: The cell number of HSC, EPC and VSEL is counted from cryopreserved UCB collected from 22 women delivered via cesarean section which already stored for more than 2 years in this study. Sample were incubated with antibodies such as cluster of differentiation (CD)34-phycoerythrin (PE)/CD45-fluorescein isothiocyanate (FITC), CD133/1 (anti-CD (AC)133)-antigen-presenting cell (APC) and, CD184 (C-X-C chemokine receptor (CXCR)4)-PE.Vio770 to detect the present of HSC, EPC and VSEL in UCB. Sample were analyze using flowcytometer BD FACS Canto II.RESULTS: The cell population of HSC and late-EPC is 0.009% and 0.01% of total cell in UCB. VSEL only represented 0.001% from total cell in UCB, showing the lowest number of cell population in UCB. The correlation between the cell number of HSC and EPC is r=0,483*, p=0.023) and between HSC and VSEL is r=0.510*, p=0.015.CONCLUSION: In this study, both EPC and VSEL have a significant positive correlation with HSC.KEYWORDS: stem cell, umbilical cord blood, endothelial progenitor, flowcytometry